Injertos óseos : nueva alternativa. Fase III. Obtención, caracterización y evaluación de hidroxiapatita sintética y el compuesto de hidroxiapatita sintética porosa – Proteínas morfogenéticas oseas en un modelo experimental lapino (2004)
ABSTRACT: The purpose of this research was to obtain synthetic Hydroxyapatite (HA) of induced porosity with osteoconductive characteristics and to mix it with Bone Morphogenetic Proteins (BMP) of osteoinductive characteristics, so they would act sinergically and would form a biocompatible graft material, able to induce differentiation of local cells to bone forming cells and at the sametime supply an osteoconductive framework that lead to new bone formation, immobilize the inductive molecule at the implantation site for a sufficient time to influence the responding cells and would act as a mechanic initial barrier for fibrous tissue ingrowth or muscle interposition in the defect, thus finally achieve new bone formation in a substantial reduced time and graft total replacement by completely autologous bone. To evaluate the characteristics of this material, a total of 20 male New Zealand rabbits with an average weight of 2.2 kg and 75 days of age were used, a rectangular osseous defect of 8 mm of diameter with equal depth at the cortex was created in the medial face of the tibia diaphysis. In a hind limb, hydroxyapatite plates of 8 mm of large and 2 mm of thickness were implanted; in the opposite hind limb the compound HA-PMO was implanted. The rabbits were distributed in 4 evaluation groups at 3, 6, 9 and 12 weeks of evolution, to evaluate the characteristics of the implant. Statistical inference of the data taken on the experiment was performed, with divided parcels design, following as basic structure of aleatorization a Completely Random Design (CRD), applying t factor (time) to main parcels (rabbits), and i factor (graft material) to subparcels (posterior limbs).